2017
DOI: 10.5130/ajceb.v17i1.5344
|View full text |Cite
|
Sign up to set email alerts
|

The Socio-Economics of Women Inclusion in Green Construction

Abstract: The female population represents one of the greatest untapped resources for economic growth and revitalization in most sectors. The purpose of the study was to examine the socio-economics of women’s inclusion in green construction. The study utilized the use of questionnaires which were distributed to female professionals in the Nigerian construction industry. A total of 120 female construction professionals were used for this study. The data gathered was analysed using SPSS v17.0 with tests such as Frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…It has been witnessed, either through primary or secondary participation, the various negative effects buildings which were not properly designed and constructed have had on both the environment and their users. Instances such as building collapses, poor building materials in buildings have affected the health of the users and other related occurrences [3], [4]. It can be boldly stated, in light with popular perspectives, that buildings must be designed and constructed with an uncompromising consideration of the safety and well-being of the users in terms of the choice of materials (how the users will react to the materials health wise) and other constructional processes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been witnessed, either through primary or secondary participation, the various negative effects buildings which were not properly designed and constructed have had on both the environment and their users. Instances such as building collapses, poor building materials in buildings have affected the health of the users and other related occurrences [3], [4]. It can be boldly stated, in light with popular perspectives, that buildings must be designed and constructed with an uncompromising consideration of the safety and well-being of the users in terms of the choice of materials (how the users will react to the materials health wise) and other constructional processes.…”
Section: Introductionmentioning
confidence: 99%
“…The research aimed at examining the anti-feminine characteristics, change towards equality and measures to balance the female identity in the construction industry. The paper presents the female stance by prioritising the perspectives of women respondents as utilised in studies such as Sang and Powell (2012) and Afolabi et al (2017). The intention is to give women a voice to describe the construction industry from a female standpoint.…”
Section: Methodsmentioning
confidence: 99%
“…The study by Afolabi et al (2017), which identified socio-economic benefits in the participation of women in green construction recognised the family/women related benefits, environment-related benefits and the green energy market-related benefits. The need for increased efforts to attract more women into the trades and construction is clearly evident.…”
Section: The Need To Balance the Female Identity In The Construction mentioning
confidence: 99%
See 1 more Smart Citation
“…Value of the data The dataset highlights sustainable strategies that can be implemented for creating safe construction activities which are environmentally friendly by construction firms and stakeholders [1] , [2] , [3] , [4] , [5] . The scientific community and researchers can use the dataset to measure the compliance and commitment of construction firms in reducing greenhouse gases (GHG).…”
mentioning
confidence: 99%